Required Elements for Success and Benefits of Participation in Camps of an On-The-Land Program in the Inuvialuit Settlement Region - Ollier, Mary; Giles, Audrey; Etter, Meghan; Ruttan, Jimmy; Elanik, Nellie; Goose, Ruth; Ipana, Esther (Études Inuit Studies, 2022)
We report on a partnership between the Inuvialuit Regional Corporation (IRC) and the University of Ottawa to determine whether/how on-the-land programming offered culturally safe experiences to meet the self-identified needs of the residents of the Inuvialuit Settlement Region. This study draws upon the experiences of participants in the IRC’s land-based healing program, Project Jewel. We used postcolonial theory supported by a decolonization framework and critical Inuit studies to direct this community-based research methodology. The community advisory committee and the research advisory team co-determined semi-structured interviews, sharing circles, and photovoice as the chosen research methods for this project. Results indicate that land-based healing programs considerably enhanced cultural identity and meaningful connections to social support and Inuvialuit heritage in an “on-the-land” environment. Land-based programs may thus offer an alternative and effective healing opportunity for participants who feel uncomfortable or are not being adequately served by conventional community-based or residential treatment programs.